On the risks of secure attachment in infancy: Childhood irritability and adolescent depression predicted by secure attachment and high approach behaviours at 14-months towards a caregiver living with inter-parental violence - Hill, Jonathan; Wright, Nicky; Sharp, Helen; Pickles, Andrew; Steele, Howard (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction The secure infant turns to a caregiver for comfort when distressed or threatened. Does this level of openness create vulnerability where the caregiver is unsupportive or aggressive? In this study we examined prospectively whether secure attachment in infancy, and approach behaviours on reunion with a parent, were associated with childhood emotional dysregulation (irritability) and adolescent depression among children exposed to inter-parental violence. Methods We followed 219 families recruited from the general population during pregnancy (members of the Wirral Child Health and Development Study; WCHADS), with attachment assessments (Strange Situation Procedure; SSP) at 14 months, maternal interviews about inter-parental violence at 2.5, 5 and 7 years, and parent and teacher rated irritability at 9 years (CBCL). At age 13 years, 199 young people rated their levels of depression (SMFQ). In addition to the standard SSP classification, a latent variable reflecting approach behaviours during reunions was generated from the SSP dimensional scores and a factor score extracted. Analyses used path analysis using the gsem command in Stata. Results There were interactions between attachment security and inter-parental violence for age 9 irritability (p = .084) and age 13 depression (p = .039) which arose from greater levels of psychopathology among secure children exposed to inter-parental violence. Similarly, higher approach behaviours during SSP reunions among children exposed to inter-parental violence were associated with irritability (interaction term p = .004) and depression (interaction term p <.001). Among children who were not exposed to partner violence higher approach behaviours in the SSP were associated with lower irritability and depression. Conclusions Infant behaviours characteristic of attachment security in the Strange Situation Procedure may not equip children to deal with exposure to inter-parental violence and associated parental negativity.